Village Digitalization: Increasing the Competitiveness of PKK Local Products Through E-Market in Balamoa Village, Pangkah District, Tegal - Adilla, Annisa; Sutjiatmi, Sri; Suparto, Diryo; afisa, Afisa (ASEAN Journal of Empowering Community, 2025)
Small and Medium Enterprises (SMEs), particularly Family Welfare Empowerment (PKK) in Balamoa Village, Tegal Regency, face serious challenges because they still rely on traditional marketing and lack digital knowledge. This condition hinders the competitiveness of local products in the wider market and is exacerbated by the accelerated adoption of e-markets after COVID-19. Data from APJII underscores this urgency, with 90% of Indonesia's 202.6 million internet users actively shopping online. Changes in consumer behavior have made the electronic market a crucial marketing channel. As a form of responsibility of the Faculty of Social and Political Sciences, Pancasakti University Tegal, the community service team offers solutions in the form of socialization and training programs. This program aims to introduce and facilitate members of the Balamoa Village PKK in utilizing the market reach of digitalized e-market products to achieve village economic independence. The program activity, titled “Village Digitalization: Enhancing the Competitiveness of Local PKK Products Through E-Market,” hopes to optimize the marketing of local products, create new jobs, and support local economic independence.